2021
DOI: 10.3389/fpsyg.2021.710736
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Engagement in Language Teaching: Investigating Self-Efficacy for Teaching Based on the Project “Sino-Greece Online Chinese Language Classrooms”

Abstract: The support of sustainable learning of foreign languages requires teacher engagement and a high level of self-efficacy, both of which are cornerstones for the persistence of teachers in carrying out teaching activities to help learning. The need for such attributes is even more crucial when online learning platforms as a mode of delivery are becoming increasingly popular. We would argue that keeping students engaged and motivated to attain their academic success online calls for the increased levels of resilie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 83 publications
1
23
0
1
Order By: Relevance
“…The blended teaching mode mandated by our department since the Covid-19 outbreak meant 20% percent of course tasks were put online and the offline instruction was reduced proportionally. Coupled with this attention loss, the internet directly connects students and learning resources ( Bao et al, 2021 ), various English courses from renowned teachers and universities on MOOC platforms offering numerous options to students and make me worried that I am going to lose my job in the near future.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The blended teaching mode mandated by our department since the Covid-19 outbreak meant 20% percent of course tasks were put online and the offline instruction was reduced proportionally. Coupled with this attention loss, the internet directly connects students and learning resources ( Bao et al, 2021 ), various English courses from renowned teachers and universities on MOOC platforms offering numerous options to students and make me worried that I am going to lose my job in the near future.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…While several studies have been conducted on different factors contributing to teachers' work engagement (e.g., Hultell and Gustavsson, 2011;Bao et al, 2021;Greenier et al, 2021), two important variables of emotion regulation and teacher resilience have received less attention. Moreover, no empirical research has probed these variables simultaneously to examine the role of emotion regulation and teacher resilience in predicting teachers' work engagement.…”
Section: Introductionmentioning
confidence: 99%
“…Student engagement has no doubt become an important issue in learning and teaching across different education institutions in recent decades (Kahu, 2013 ; Lim, 2017 ; Bao et al, 2021 ; Harris and Leeming, 2021 ; Rahimi and Zhang, in press ). Many studies have shown that student engagement is related to student satisfaction and experience, their learning outcomes and achievements (Pascarella and Terenzini, 2005 ; Carini et al, 2006 ; Lei et al, 2018 ; Teng and Zhang, 2018 , 2020 ; Gan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%